Alzheimer's disease - etiology and pathogenesis - Wróbel, Grzegorz; Zieliński, Paweł; Spałek, Jakub (Journal of Education, Health and Sport, 2017)
Alzheimer's disease (AD) is one of the neurodegenerative diseases of the senile age that is most prevalent in the modern world. With regard to the population of people aged 60 years, the incidence of Alzheimer's disease is estimated at 1%, while in the population of people aged 90 and over even up to 50%. This type of dementia causes serious deficits in cognitive functions. From the neuroanatomical point of view, the changes taking place in the brain are the result of the disappearance of areas within the hippocampus, additionally, as one of the key causes of this disease, the accumulation of beta-amyloid in brain tissue is considered. The consequence of many changes is the loss of neurons, aggregation of amyloid plaques and the formation of tau protein into tangles. There are many hypotheses regarding the mechanisms and causes of the AD, but there are still many doubts about the existing health problem of older people. The aim of the study is to investigate the etiology and pathogenesis of AD in the context of the current state of knowledge and possible prognoses for the future in the light of research into this disease.